Students’ Emotional Enggagement in Reading Comprehension Through Read, Cover, Remember and Retell (RCRR) Strategy - Arahman, Fahmi Rizqi; Kamil, Acep Bahrum; Sumartra, Sumartra (EDULIA: English Education, Linguistic and Art Journal, 2024)
This research purposes are to find out how the student’s emotional engagement towards in the use of read, cover, remember and retell strategy in Reading comprehension This student uses qualitative research with design case study. In this study researcher conduct research at Indonesia public junior high school in a town in west java. the participant 6 student in one class for collecting data researcher used observation and interview. This research carries four main findings, they are: 1) RCRR strategy crates student interest in reading comprehension in reading comprehension; 2) RCRR strategy creates a positive emotions and enjoyable learning. these findings substantiate the notion that the RCRR strategy not only enhances reading comprehension outcomes but also enriches the emotional dimension of learning. By fostering interest, engagement, and positive emotions, the strategy emerges as a valuable approach in promoting holistic and effective learning experiences within the realm of reading comprehension. As educators seek to optimize instructional methods, the RCRR strategy offers a promising avenue to elevate both student engagement and comprehension outcomes. Keywords: Cover, Read, Reading Comprehension, Remember and Retell (RCRR) Strategy, Student emotional Engagement